(untitled) (JURNAL KEPERAWATAN, 2018)
Abstract: Patients with mental disorders in rehabilitation periods treated by their own family at home or outpatient need support to comply with the treatment program. Families may reduce anxiety caused by certain diseases and may reduce the temptation to non-compliance with continuity of treatment. The purpose of this study was to determine the relationship of family support with medication adherence. The research design was analytical descriptive with Cross Sectional approach. The sampling technique used simple random sampling with 37 samples. The result of chi square statistic test with 95% confidence level (Î± = 0,05) obtained result p value 0,000 <0,05. The conclusion is that there is a relationship of family support with the adherence of taking the medicine for schizophrenic patients in Prof. hospital. Dr. V. L. Ratumbuysang North Sulawesi province. Dr. V. L. Ratumbuysang must prepare special health workers to provide health educational in poly psychiatry when family and patient come for treatment. Keywords: Family Support, Drug Compliance, Schizophrenia Abstrak: Pasien gangguan jiwa dalam masa rehabilitasi yang dirawat oleh keluarga sendiri dirumah atau rawat jalan memerlukan dukungan untuk mematuhi program pengobatan. Keluarga dapat mengurangi ansietas yang disebabkan oleh penyakit tertentu dan dapat mengurangi godaan terhadap ketidakpatuhan kontinuitas pengobatan.Tujuan penelitian ini untuk mengetahui hubungan dukungan keluarga dengan kepatuhan minum obat. Desain penelitian menggunakan deskriptif analitik dengan pendekatan Cross Sectional. Teknik pengambilan sampel menggunakan simple random sampling dengan jumlah sampel 37 orang. Hasil uji statistik chi square dengan tingkat kepercayaan 95 % (Î± = 0,05 ) diperoleh hasil p value 0,000 < 0,05. Simpulan yaitu terdapat hubungan dukungan keluarga dengan kepatuhan minum obat pasien skizofrenia di rumah sakit Prof. Dr. V. L. Ratumbuysang provinsi Sulawesi Utara.Saran pihak rumah sakit Prof. Dr. V. L. Ratumbuysang harus menyiapkan tenaga kesehatan yang khusus memberikan health educational di poli psikiatri saat keluarga dan pasien datang berobat. Kata Kunci: Dukungan keluarga, Kepatuhan minum obat, skizofrenia